The effect of students' motivation and behavior to the learning environment and it implication to students' achievement in learning English - Is Dewangga; Nasaruddin Nasaruddin (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2020)
This research aims to find out the answer of the hypothesis about the effect of students' motivation and behaviour to the learning environment and it implication to students' achievement in learning English. Survey causal was the approach of this research by using path analysis. Structure Equational Analysis by using LISREL was used to analyse the data. The population was 320 students and the sample was 177 students taken randomly. The result hypothesis was: (1) There was an effect of learning motivation (X1) to learning behaviour with the Value = 8.99 > t t = 1.984; (2) There was an effect of motivation to learning attitude with the value to= 5.30 >t t = 1.984 (3) There was an effect of learning behaviour to learning environment with the value= 11.92 > tt = 1.984 (4) There was an effect of students’ learning motivation to learning environment with the value to= 4.25 > tt = 1.984 (5) There was an effect of students’ learning behaviour to learning environment with the value to= 7.74 > tt = 1.984 (6) There was an effect of students’ learning motivation to learning achievement in learning English with the value = 5.25 > tt = 1.984 (7) There was an effect of learning behaviour to learning achievement in learning English with the value to= 7.61 > tt = 1.984 (8) There was an effect of learning behaviour to learning achievement in learning English (Y) with the value to= 2.23 > tt= 1.984 (9) There was an effect of learning environment to slearning achievement in learning English with the value = 6.44 > tt = 1.984. The correlation test model was a fit model with the value of Chi-Square = 0, 05 and P was 1 (P > 0,00).